Estradiol Treatment Prevents Injury Induced Enhancement in Spinal Cord Dynorphin Expression - Gupta, Daya S.; Hubscher, Charles H. (Frontiers in Physiology, 2012)
Administration of the ovarian steroid estradiol in male and female animals has been shown to have neuromodulatory and neuroprotective effects in a variety of experimental models. In the present study, spinal tissues from dermatomes just above (T5-7, “at level”) a severe chronic spinal cord injury (SCI) at T8 were analyzed for expression levels of prodynorphin (PRDN) and phospho-(serine 369) К-opioid receptor (KOR-P) in 17 β estradiol (EB)- and placebo-treated adult male rats. Dynorphin was targeted since 1) it has previously been shown to be elevated post-SCI, 2) intrathecal injection of dynorphin produces several of the same adverse effects seen with a SCI, and 3) its increased expression is known to occur in a variety of different experimental models of central neuropathic pain. A significant elevation of extracellular levels of both PRDN and KOR-P in the placebo-treated SCI group relative to uninjured surgical sham controls was found in spinal tissues above the injury level, indicating increased dynorphin levels. Importantly, the EB-treated SCI group did not show elevations of PRDN levels at 6 weeks post-injury. Immunohistochemical analysis of at level tissues revealed that EB treatment significantly prevented a post-SCI increase in expression of PRDN puncta co-labeling synapsin I, a nerve terminal marker. The dynorphin containing terminals co-labeled vesicular glutamate receptor-2 (a marker of glutamatergic terminals), a finding consistent with a non-opioid basis for the adverse effects of dynorphin. These results support a beneficial role for EB treatment post-SCI through a reduction in excessive spinal cord levels of dynorphin. Current studies manipulating the timing of the EB treatment post-injury along with specific functional assessments will address whether the beneficial effects are due to EB’s potential neuromodulatory or neuroprotective action.